THE ROLE AND IMPORTANCE OF USE OF ELECTRONIC TEXTBOOKS IN TEACHING SPECIAL SUBJECTS - Maftuna Juraeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Electronic information and educational resources have been created for teachers - programs on the use of modern technologies in educational institutions. It serves to improve the quality of teaching and improve the qualifications of teachers. The work to create, develop, and popularize multimedia programs is bearing fruit. In educational institutions, students are exposed to scientific information directly on the Internet or in classrooms using CDs and audio CDs. Today, the ranks of our youth are expanding, freely using modern information technologies and surprising the peoples of the world with their potential. All this is the result of the broad conditions and favorable opportunities created for youth in our country.